Bio-ceramic coatings adhesion and roughness of biomaterials through PM-EDM: a comprehensive review. Issue 11 (17th August 2020) - Al-Amin, Md; Abdul Rani, Ahmad Majdi; Abdu Aliyu, Abdul Azeez; Bryant, Michael G; Danish, Mohd; Ahmad, Azlan
ABSTRACT: Powder mixed-EDM is a newly emerging proposed manufacturing process which can simultaneously shape and coat the surface of conductive materials. Transformation of machined surface is occurred through melting and chemical reactions of the added powders, tools materials and dielectric fluid due to elevated temperature generation during the operation. Though the biomaterials such as titanium alloy, magnesium, 316 L SS and Co-Cr alloy attribute to higher mechanical strength, corrosion and wear resistance, and enough biocompatibility, these are limited to apply directly because of releasing the toxic elements and having inferior biological responses. Surfaces of bio-implants made from these biomaterials are therefore protected using bioactive and biocompatible coating. Hydroxyapatite is a bioceramic that possesses bone like element composition and excellent biocompatibility. The PM-EDM process with hydroxyapatite can enhance not only adhesion strength and roughness but also biocompatibility of the treated surface. It is proposed in this paper that carbide and oxide coating formation can improve the microhardness, bonding strength and roughness of surface of the substrates. This study comprehensively reports the current status of adhesion and surface coarseness of bio-ceramics based coating through PM-EDM process. A comparative critical analysis of employing bio-ceramic powder using various deposition techniques is presented in this review.